The Impact of Sleep Disorders on Neurodegenerative Recovery - Chorshanbiyevich, Choriev Abubakr; Ahmadovna, Quyliyeva Nasiba (American Journal of Bioscience and Clinical Integrity, 2025)
This article examines the impact of sleep disorders on neurodegenerative recovery. The clinical data of 71 patients were analyzed within the scope of the study. Attention was focused on the relationship between sleep quality and duration and the process of neuronal recovery. Global and Uzbek contexts of the issue were studied, highlighting the main mechanisms of sleep disorders and their influence on neurodegeneration.